Bay of Bengal cyclone cluster of November 1992 (MAUSAM, 1998)
The cyclone cluster that formed over the Bay of Bengal during November 1992 has been looked into in relation to sea surface temperature (SST) distribution obtained from long. 1°x1° grid averages remotely sensed by NOAA-AVHRR. Examination of weekly SSTs has revealed that entire Bay of Bengal north of 8°N was unusually warmer about a week before the foundation of the cyclone cluster. As a matter of fact, during the above period the SST for each of the 60 grids over the sea area between 13°- 21° and 81°- 90°E exceeded 30°C. Widespread cooling of the sea was noticed just before the commencement of cyclogenesis.